Penang Museums, Culture and History - Abu Talib Ahmad (Kajian Malaysia, 2015)
The essay studies museums in Penang, their culture displays and cultural contestation in a variety of museums. Penang is selected as case study due to the fine balance in population numbers between the Malays and the Chinese which is reflected in their cultural foregrounding in the Penang State Museum. This ethnic balance is also reflected by the multiethnic composition of the state museum board. Yet behind this façade one could detect the existence of culture contests. Such contests are also found within the different ethnic groups like the Peranakan and non-Peranakan Chinese or the Malays and the Indian-Muslims. This essay also examines visitor numbers and the attractiveness of the Penang Story. The essay is based on the scrutiny of museum exhibits, museum annual reports and conversations with former and present members of the State Museum Board.